2023
DOI: 10.1002/jvc2.107
|View full text |Cite
|
Sign up to set email alerts
|

The comprehensive impact of pityriasis rubra pilaris on physical symptoms, mental health, and activities of daily living: A mixed methods study

Abstract: Background Pityriasis rubra pilaris (PRP) is a rare and often severe inflammatory skin disorder with major detriment to patients' quality of life. While past studies have described in detail the morphologic and histopathologic presentations of PRP, little attention has been given to the patient experience. Objectives To identify the physical, mental, and daily living impacts of patients living with PRP Methods Four focus groups involving 47 participants with PRP from six countries were conducted in English. Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…A recently published study found that depression is common after diagnosis with PRP, along with a considerable impact on daily living. 5 Additional studies should be conducted to outline the range of impacts PRP has on an individual’s life, allowing clinicians and patients an improved understanding of the expected disease course and support needed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recently published study found that depression is common after diagnosis with PRP, along with a considerable impact on daily living. 5 Additional studies should be conducted to outline the range of impacts PRP has on an individual’s life, allowing clinicians and patients an improved understanding of the expected disease course and support needed.…”
Section: Discussionmentioning
confidence: 99%
“…Atypical juvenile (Type V) PRP, known as familial PRP, has been potentially linked to Caspase Recruitment Domain Family Member 14 (CARD14) gene mutations. 5 HIV-associated (Type VI) PRP is associated with nodular acneiform lesions, lichen spinulosus-like lesions, and erythroderma. This type is often resistant to therapy and has poor prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…Pityriasis rubra pilaris (PRP) is a rare, often severe, inflammatory papulosquamous disorder characterized by widespread erythematous plaques, furfuraceous scaling, and painful palmoplantar keratoderma with fissuring. PRP has a high degree of morbidity, with a high risk of passive or active suicidality …”
Section: Introductionmentioning
confidence: 99%
“…PRP has a high degree of morbidity, 1 with a high risk of passive or active suicidality. 2 The pathogenesis of PRP is incompletely understood, but genetic pathways have a strong overlap with psoriasis, 3 including overexpression of interleukin (IL)-23, 4 a proinflammatory cytokine that most prominently activates T helper 17 (Th17) cells. Guselkumab (Tremfya; Janssen Research & Development) binds IL-23p19 and is approved by the US Food and Drug Administration to treat adults with moderate to severe psoriasis.…”
mentioning
confidence: 99%